Women images - Jain, Pratibha, 1940-; Mahan, Rajan (Jaipur : Rawat Publications, 1996)
Contributed articles.
Includes passages in Sanskrit.
Includes bibliographical references and index.
Keywords: Women -- India; Women -- India -- Social conditions; Women -- India -- Literary collections